The efect of various fuels on the yield, structural and optical properties zinc zirconate nanocomposite - Musembi, Michael K.; Dejene, Francis B.; Ahemen, Iorkyaa; Tshabalala, K. G. (Springer Berlin Heidelberg, 2020)
Various types of fuels were used in a low-temperature solution combustion synthesis of zinc zirconate nanocomposite at a pH of 7. In the synthesis, the fuels used were citric acid, glycine, urea, hydrazine hydrate, and ammonium nitrate while zirconium butoxide and zinc nitrate were the precursor sources of Zr4+ and Zn2+ ions, respectively. The samples were calcined for 2 h at a temperature of 600 °C. The study of the structural properties showed varied morphologies ranging from highly agglomerated surfaces, crystalline aggregates as well as nanorods. There was a gradual growth of zinc zirconate perovskite within phases of zirconia and zinc oxide. It was observed that there were prominent photoluminescence emissions spread from violet-blue into the yellow-white regions with peaks varying from about 400 to 490 nm. The energy bandgap of the nanocomposites was between 2.93 and 3.22 eV depending on the fuel used in the preparation of the sample.
Keywords: Nanocomposite; Stoichiometric fuel ratio; Zinc zirconate; Solution combustion synthesis; Perovskite